2011
DOI: 10.1093/hmg/ddr526
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Parkinson disease mutations enhance its microtubule association

Abstract: Dominant missense mutations in leucine-rich repeat kinase 2 (LRRK2) are the most common genetic causes of Parkinson disease (PD) and genome-wide association studies identify LRRK2 sequence variants as risk factors for sporadic PD. Intact kinase function appears critical for the toxicity of LRRK2 PD mutants, yet our understanding of how LRRK2 causes neurodegeneration remains limited. We find that most LRRK2 PD mutants abnormally enhance LRRK2 oligomerization, causing it to form filamentous structures in transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
218
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(235 citation statements)
references
References 36 publications
17
218
0
Order By: Relevance
“…Recently, it was suggested that LRRK2 PD mutations cause defects in nuclear envelope organization (34). It was previously observed that LRRK2 PD mutant proteins accumulate on microtubules in primary neurons (35). In addition, several studies have implicated LRRK2 in the autophagy pathway (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that LRRK2 PD mutations cause defects in nuclear envelope organization (34). It was previously observed that LRRK2 PD mutant proteins accumulate on microtubules in primary neurons (35). In addition, several studies have implicated LRRK2 in the autophagy pathway (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Yet filopodial outgrowth is not just a function of actin dynamics and stability but it is also tightly controlled by the tubulin cytoskeleton. LRRK2 also directly interacts with microtubules by binding to beta-tubulin (Gandhi et al, 2008;Gillardon, 2009a;Kett et al, 2012;Law et al, 2014). The G2019S mutation in the kinase domain markedly increases LRRK2-mediated beta tubulin phosphorylation (Gillardon, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Several LRRK2 mutations cause a reduction in neurite growth that is rescued by LRRK2 inhibition [37-40], suggesting that LRRK2 influences the cytoskeleton. Kett et al [41] reported that most LRRK2 mutations enhance LRRK2 oligomerization and generate microtubule-associated filamentous structures in cells. Godena et al [42] found that LRRK2 containing ROC-COR mutations (R1441C and Y1699C) mainly binds to deacetylated microtubules and that deacetylase inhibitors and tubulin acetylase block this association.…”
Section: Lrrk2 Mutations and Their Mechanisms Of Actionmentioning
confidence: 99%